The environment in world history - Mosley, Stephen (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2010)
"Covering the past 500 years of global history, The Environment in W orld History examines the processes that have transformed the earth and have put growing pressure on natural resources." "The Environment in W orld History also examines how European expansion overseas brought abou t a fundamental reorganisation of the world's ecology as contact betwee n long-isolated continents was re-established. It offers a fresh enviro nmental perspective on familiar world-history narratives of imperialism and colonialism, trade and commerce, and technological progress and th e advance of civilisation, and will be invaluable reading for all stude nts of world history and environmental studies."--BOOK JACKET.
Introduction: Environment and history -- The world hunt -- Forests a nd forestry -- Soils and irrigation -- Cities and the environment -- Co nclusion: Beyond the limits?
Includes bibliographical references and index.
Keywords: Human ecology -- History; Nature -- Effect of human beings on -- History; World history; Human ecology -- Case studies; Nature -- Effect of human beings on -- Case studies